THE EFFECT OF FILLER CONCENTRATION VARIATIONS AND DRYING TEMPERATURE ON JUWET (SYZYGIUM CUMINI) POWDER INSTANT DRINK - Muyassaroh; Nilna Minah, Faidliyah; Setyawati, Harimbi; Junita, Erni (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2022)
Juwet fruit has a sour taste. The purple color of this ripe juwet comes from anthocyanins. Anthocyanins in fruit or vegetables can appear as red, purple, or blue, depending on the acidity (pH) conditions. Anthocyanins also act as a source of antioxidants. Antioxidants from anthocyanins are relatively safer than synthetic antioxidants that allow the promotion of carcinogenesis. Antioxidants will stimulate the body's system response to destroy free radicals. The magnitude of the benefits of antioxidants has encouraged many researchers to lift the natural potential with high antioxidant content to be processed into practical and easy dishes. Therefore, Juwet fruit processing is needed to increase public acceptance of Juwet fruit, one of which is by removing tannins from Juwet fruit by blanching and processing juwet fruit into instant powder that is practical and easy to consume. Both in the process of evaporation and drying. The purpose of this research is to increase the economic value of Juwet fruit as an instant powder drink which is rich in vitamins and high in antioxidants. Optimization of the process is carried out by combining the evaporation and drying processes to obtain products that comply with SNI standards. From the results of this study, the highest Vitamin C content was obtained at a drying temperature of 500C, which was 0.128%/1 g with an antioxidant reactivity of 50%.